2006
DOI: 10.1080/09637480600801837
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of leaves of some genotypes of mulberry (Morus alba)

Abstract: This study was undertaken to determine the proximate composition, vitamins, minerals and the antinutritional factor tannic acid in leaves of six genotypes of mulberry. The results showed that in fresh mulberry leaves the proximate composition values ranged from 71.13 to 76.68% for moisture, from 4.72 to 9.96% for crude protein, from 4.26 to 5.32% for total ash, from 8.15 to 11.32% for Neutral Detergent Fiber (NDF), from 0.64 to 1.51% for crude fat, from 8.01 to 13.42% for carbohydrate and from 69 to 86 kcal/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 4 publications
2
88
2
Order By: Relevance
“…Genus Morus (mulberry) is one such example that consists of over 150 species; among them Morus alba L. is dominant [25]. Mulberry leaf (the leaf of Morus alba) commonly used in the silkworm diet, has been used in edible foods.…”
Section: Introductionmentioning
confidence: 99%
“…Genus Morus (mulberry) is one such example that consists of over 150 species; among them Morus alba L. is dominant [25]. Mulberry leaf (the leaf of Morus alba) commonly used in the silkworm diet, has been used in edible foods.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the leaves and fruits contain 15-31% high quality protein, crude fiber, 200-300 mg/100g of ascorbic acid, of which over 90% is present in the reduced form, vitamin B, folic acid, folinic acid and vitamin D, β-carotenes and trace minerals (iron, zinc, calcium, potassium, phosphorous, magnesium) (Sharma & Madar 1994;Srivastava et al 2006;Ercisli & Orhan 2007). Moreover, there is a lot of flavonoids (quercetin, rutin, isoquercitrin, astragalin, kuwanon G and C, catechin, mulberrofuran G, albanol B, morusin, sanggenon B and D), which exhibit strong antioxidant activity (Yen et al 1996;Kofujita et al 2004), antifungal and antibacterial potential against harmful strains of bacteria Bacillus, Staphylococcus, Escherichia and Streptococcus (Shirata 1982;Park et al 2003) and against viruses Herpes simplex type 1 (HSV-1) (Kimura et al 2007;Butt et al 2008).…”
Section: The Potential Of White Mulberrymentioning
confidence: 99%
“…Most parts of the mulberry are used in the food industry, including the leaves in teas, infusions, and as vegetables (Sývacý and Semen, 2004;Paredes-López et al, 2010;Łochyńska, 2015). It has been reported that mulberry leaves are rich in proteins, carbohydrates, fats, mineral elements, and vitamins (Srivastava et al, 2006;Butt et al, 2008;Adeduntan and Oyerinde, 2009).…”
Section: Introductionmentioning
confidence: 99%